The Use of a Modern Algorithm for Prevention of Late Complications in Acute Poisoning with Acetic Acid - R. N. Akalayev; A. A. Stopnitsky (Неотложная медицинская помощь)
Acetic acid has a local cauterizing effect like coagulation necrosis and significant resorptive hemato-, nephro- and hepatotoxic effect due to hemolysis of erythrocytes, development of toxic coagulopathy, syndrome of disseminated intravascular coagulation. Developing severe hypoxia, microcirculation disorder, and impaired liver and kidney function significantly worsen proliferative processes in the area of chemical burn, leading to the development of such serious complications as late esophageal and gastric bleeding and cicatrical stenosis of the esophagus and stomach. Therefore, the prevention of these complications should include not only local treatment of the burn surface, but also complex therapy aimed at restoring the function of affected organs at the early hospital stage and rehabilitation stage. The article describes the case of practical application of an intensive care algorithm, which includes the use of microcirculation improvers, Cytoflavin — an antihypoxant on the basis of succinic acid, Actovegin — a stimulant of proliferation, prolonged use of glucocorticoids, active nutritional support with a protein-carbohydrate mixture, all initiated upon arrival.